SETRATEGI KOMUNIKASI DALAM PROSES BHí‚KALAN ETNIK MADURA DI DAERAH TAPAL KUDA - Haryono, Akhmad (LITERA, 2018)
This article aims at describing the communication strategy used by Madurese ethnic members in Tapal Kuda regions in bhí¢kalan process. For this aim, the linguistic approach was used in this research. The data were collected with participatory observation such as interview, recording, and documentary study. The collected data were then transcripted into the written data and analyzed using discourse analysis with pragmatic concept. The research result indicated that Madurese language (ML) used in bhí¢kalan process constitutes ML variation of èngghi-enten (ML È-E) ,èngghi-bhunten (ML È-B), and íªnja’-iya (ML íŠ-I). The rhetorical style used in bhí¢kalan process is indirect rhetorical style, that is figurative language. Pangadí¢’ (delegation) is compared to vegetation, animal, and wind. Language variation (as politeness form) and rhetorical style are used as communication strategy in bhí¢kalan process.